2015
DOI: 10.1097/sap.0000000000000383
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Patient Registries in Breast Surgery

Abstract: The TOPS and NSQIP capture significantly different patient populations, with TOPS' self-reported data allowing for the inclusion of private practices. This self-reporting limits TOPS' ability to identify medical complications; surgical complications and readmissions, however, were not underreported. Many surgical complications are captured by TOPS at a higher rate due to its broader definitions, and others are not captured by NSQIP at all. The TOPS and NSQIP provide complementary information with different str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…As has been highlighted in previous literature, the NSQIP and TOPS exhibit unique strengths and weaknesses. 20 , 28 , 29 The validity of the NSQIP has been documented extensively. It has been shown that there is very limited (<2%) disagreement among data collectors and auditors of the NSQIP when considering nearly all of the multiple hundred variables included in the dataset.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As has been highlighted in previous literature, the NSQIP and TOPS exhibit unique strengths and weaknesses. 20 , 28 , 29 The validity of the NSQIP has been documented extensively. It has been shown that there is very limited (<2%) disagreement among data collectors and auditors of the NSQIP when considering nearly all of the multiple hundred variables included in the dataset.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that there is very limited (<2%) disagreement among data collectors and auditors of the NSQIP when considering nearly all of the multiple hundred variables included in the dataset. 3 , 20 , 31 , 32 Moreover, rates of surgical outcomes have been validated in single-institution studies. 31 Importantly, the NSQIP sampling methodology produces what can be considered a random sample of surgical cases conducted at US hospitals, making results interpretable and generalizable to a national population of surgical cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations